The affordances of images in digital reflective writing: an analysis of preservice teachers' blog posts. Issue 4 (3rd July 2020) - Birello, Marilisa; Pujola Font, Joan Tomas
ABSTRACT: The aim of this study is to examine the affordances of images to prompt reflective processes of preservice teachers writing in a digital environment. The study was conducted over three academic years and a total of 180 preservice teachers were asked to write a blog post to reflect on how they learn to write and their approach on teaching children how to write. This study analyses the type of images used in the blog posts and the logico-semantic relationships between the images and the written text. The core data were gathered from the preservice teachers' blog posts, and then triangulated with the individual written reflections and with the group recordings analysing their respective posts. The results indicate that the blog posts in which preservice teachers use images either connected to personal experiences or with a metaphorical effect, the image-text relation enhances their reflections; whereas the most neutral images that illustrate the act of writing give no added value to their reflections. The discussion addresses the issues on how to help preservice teachers to use images in digital writing in a meaningful way that can deepen their reflective processes.